Non-specific Lipid Transfer Proteins in Legumes and Their Participation During Root-Nodule Symbiosis - Fonseca-García, Citlali; Solis-Miranda, Jorge; Pacheco, Ronal; Quinto, Carmen (Frontiers in Agronomy, 2021)
Non-specific lipid transfer proteins (LTPs) constitute a large protein family in plants characterized by having a tunnel-like hydrophobic cavity, which allows them to transfer different lipid molecules. LTPs have been studied in various model plants including those of agronomic interest. Recent studies have demonstrated that LTPs play key functions in both biotic and abiotic stress. In plants-pathogen interaction, they act as either positive or negative regulators of defense responses. However, little is known about the roles of LTPs in symbiotic interactions, especially in root nodule symbiosis. Here, we performed a broad genome analysis of LTP family members in legumes and other important model plants, focusing on their possible roles in legume-rhizobium symbiosis. In silico analysis showed that legumes contain large LTP families, with at least 70 LTP members clustered into four clades. Although the structures of LTP genes and proteins are conserved among species, differences were observed between clades from different species. LTPs are widely expressed in different plant tissues. In general, genes of the LTP1 and LTP2 classes are highly expressed in shoot and reproductive tissues in all analyzed species. Furthermore, genes of the different classes are also expressed in roots inoculated with rhizobia and nodules of legumes. RT-qPCR expression profile analysis of seven PvLTP genes in common bean (Phaseolus vulgaris) revealed that these genes are differentially expressed during the early and late stages of nodulation and they are genetically regulated by PvRbohA. These findings provide insight into the putative roles of LTP family members in legume-rhizobium symbiosis and their possible interactions with RBOH-dependent ROS production.